The expert’s estimates application in the preparation of city general plan - Bardauskienė, Dalia (Technological and Economic Development of Economy, 2007)
The future of Lithuanian cities depends on a territorial planning system that is being constantly improved by the market factors and maturing democratic society. After the restoration of independence, cities underwent significant urban transformations, that lacked a clear strategy, and urban General Plans, the preparation of which intensified only after Lithuania’s accession to the European Union. A limited work of general planning revealed strengths and weaknesses of the Lithuanian territorial planning system but failed to provide a clear, measurable answer how well this system meets European urban guidelines, market expectations and society’s aspirations. In the absence of indicators, we have to rely upon the opinion of citizens and experts which is often different, unverified and therefore it is unclear whose interests these opinions reflects ‐ those all of the city or individual economically strong and politically influential interest groups. It is under these circumstances the second General Plan of Vilnius City to the year 2015 was drawn up after the restoration of independence. The plan was prepared by applying new planning methods based on citizens’ and experts’ poll results and broad public participation process. The reliability of the results of polls in Vilnius General Plan was estimated by applying mathematical methods. It showed great agreement among the experts’ opinions. Therefore it can be stated that solutions of the General Plan meet interests of its citizens. The tendency of the business world to evaluate territorial planning and urban problems is differently than urban developers, economists or scientists. Differently from business, citizens are more conservative in estimating the possibilities for new development and reconstruction in existing residential areas, but this opinion is not unanimous and is dependent on social economic factors (age, income, time of living in the city). Therefore a conclusion can be made that methods applied in city general planning process have enabled the preparation of a new high quality Vilnius City General Plan until 2015. Plan reflects the interests of all, of its citizens rather than individuals. The implementation of the General Plan is going to be successful if, first of all vital urban deformations are handled properly and problems of territory planning and public involvement, which are turning into systematic ones, are solved at the national level. Article in Lithuanian. Ekspertinių vertinimų taikymas rengiant miesto bendrąjį planą Santrauka. Lietuvos miestų ateitis priklauso nuo teritorijų planavimo sistemos, kurią tobulina laisvėjanti rinka ir demokratėjanti visuomenė. Po nepriklausomybės atkūrimo miestai pergyveno dideles urbanistines transformacijas, kurios dažnai vyko be aiškios strategijos ir bendrųjų planų, kurių rengimas suaktyvėjo tik Lietuvai tapus Europos Sąjungos nare. Pirmieji bendrojo planavimo darbai atskleidė Lietuvos teritorijų planavimo sistemos tendencijas, tačiau nedavė pagrįsto atsakymo, kiek sistema atitinka darniosios plėtros tikslus. Neaišku, kieno interesams atstovauja ir miestų teritorijų planavimo proceso dalyviai – viso miesto ar ekonomiškai ir politiškai įtakingų asmenų, lobistinių grupių. Šioje situacijoje parengtas antras po nepriklausomybės atkūrimo Vilniaus miesto bendrasis planas. Planavimo metodika, paremta gyventojų ir ekspertų apklausų rezultatais ir viešu procesu, leido nustatyti vidinius ir išorinius miesto plėtros veiksnius, urbanistinių struktūrų deformacijas ir pagrįsti sprendinius. Taikant matematinius metodus patikrinti Vilniaus bendrojo plano ekspertų apklausos rezultatai. Tyrimai parodė aukštą ekspertų nuomonių suderinamumą ir tai, kad verslo nuomonė skiriasi nuo urbanistų, ekonomistų ar mokslininkų. Skirtingai nei verslininkai, miesto gyventojai rezervuotai vertina naujos plėtros ir rekonstrukcijos galimybes esamuose gyvenamuosiuose rajonuose, tačiau ši nuomonė priklauso nuo socialinių ekonominių veiksnių (amžiaus, sėslumo, pragyvenimo lygio). Daroma išvada, kad nauja bendrojo planavimo metodika, paremta ekspertinio vertinimo metodais, leido parengti aukštos kokybės Vilniaus miesto bendrąjį planą iki 2015 metų. Bendrasis planas atspindi viso miesto visuomenės interesus ir sudaro galimybę siekti darniosios plėtros. Įgyvendinimo sėkmė priklauso nuo to, kaip greitai bus išspręstos nacionalinio lygmens teritorijų planavimo sistemos problemos (sukurta urbanistinė politika, iš esmės tobulinama teisinė norminė bazė ir viešas planavimo procesas) ir nuosekliai mažinami skirtumai tarp miesto centro ir pakraščių. Reikšminiai žodžiai: darnioji plėtra, teritorijų planavimas, bendrasis planas, ekspertiniai vertinimai, nuomonių suderinamumas ir priklausomybė nuo socialinių ekonominių veiksnių. First Published Online: 21 Oct 2010